Upgrading and Surface Coating of Egyptian White Sand with Polymers and Silanes (Rudarsko-geološko-naftni zbornik, 2024)
Egypt is endowed with huge reserves of filler minerals, such as silica sand which form approximately 95% of the Earth's crust. The silica sand industry is used in many fields, such as pharmaceutical practices, chemicals, glass, ceramics, electronics, and photovoltaic industries. The aim of this study is to remove impurities from silica sand and apply surface modification processes to enhance its value for various industrial manufacturing applications. Various processing techniques, including classification, attrition scrubbing, magnetic separation, ultra-fine grinding and surface modification, were conducted throughout the study. The results indicated that attrition scrubbing to the classified size fraction of -0.6 + 0.1 mm was capable of reducing the iron concentration from 0.068% to 0.045%. Utilizing the Box-Behnken design, the optimal conditions for magnetic separation were identified, resulting in a decrease in iron content down to 0.012%. Simultaneously, the silica content increased from 99.05% to 99.76%. The results of ultrafine grinding using an attritor mill revealed that a grinding time of 2 hours is sufficient to reach a size suitable for the coating process. Surface modification of the produced ultrafine sand was conducted using polymers and silanes. The treated sand was characterized using SEM, zeta potential, adsorption density, and FTIR measurements. Notably, hydrophobicity increased, accompanied by an increase in particle size. Simultaneously, the surface becomes flatter, indicating the formation of a thin layer. Consequently, the coated sand proved to be a satisfactory material that met the criteria to be used as a filler in coating and paints.